Perlindungan Hukum Bagi Yayasan Terhadap Penyalahgunaan Penggunaan Donasi Sosial Oleh Penerima Donasi - Muhamad Farudin; Haidar Hisyam Setiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
This research paper discusses the legal protection for foundations against the misuse of social donations by recipients, using the case of Agus Salim and the Yayasan Rumah Peduli Kemanusiaan as a focal point. Legal protection is essential in ensuring justice, security, and legal certainty for individuals and organizations, particularly in the context of non-profit foundations that play a crucial role in channeling donations to those in need. The misuse of social donations poses significant risks, not only causing financial losses but also damaging the foundation's reputation and public trust. This study employs a normative legal research method to analyze the relevant legal aspects, including laws governing foundations and social donations, while emphasizing the need for effective legal mechanisms to safeguard foundations against such abuses. The findings highlight the critical role of legal frameworks in preventing and addressing misuse, ensuring that donations are utilized according to their intended social purposes. Ultimately, this research aims to contribute to the understanding of legal responsibilities and protections for foundations, promoting transparency and accountability in social donation management.